2011
DOI: 10.1111/j.1365-2958.2011.07569.x
|View full text |Cite
|
Sign up to set email alerts
|

FMP30 is required for the maintenance of a normal cardiolipin level and mitochondrial morphology in the absence of mitochondrial phosphatidylethanolamine synthesis

Abstract: SummaryMitochondria of the yeast Saccharomyces cerevisiae contain enzymes Crd1p and Psd1p, which synthesize cardiolipin (CL) and phosphatidylethanolamine respectively. A previous study indicated that crd1D is synthetically lethal with psd1D. In this study, to identify novel genes involved in CL metabolism, we searched for genes that genetically interact with Psd1p, and found that deletion of FMP30 encoding a mitochondrial inner membrane protein results in a synthetic growth defect with psd1D. Although fmp30D c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…1, A and B). This result is consistent with recent findings that Psd1 is required for normal mitochondrial morphology (4,5). To further define the mitochondrial aggregation phenotype, we performed electron microscopic analysis.…”
Section: Psd1 Is Required For Normal Mitochondrial Morphology-tosupporting
confidence: 90%
See 1 more Smart Citation
“…1, A and B). This result is consistent with recent findings that Psd1 is required for normal mitochondrial morphology (4,5). To further define the mitochondrial aggregation phenotype, we performed electron microscopic analysis.…”
Section: Psd1 Is Required For Normal Mitochondrial Morphology-tosupporting
confidence: 90%
“…Whereas the protein machineries of mitochondrial fusion and fission have been extensively studied, the role of lipids in regulating these processes is just beginning to be uncovered. It has been shown that non-bilayer-forming lipids such as phosphatidic acid, cardiolipin (CL), 3 and phosphatidylethanolamine (PE) are required for proper mitochondrial morphology (1)(2)(3)(4)(5)(6). Recently, a study examining the loss of both CL and PE by deleting CL synthase, CRD1, and the mitochondrial phosphatidylserine decarboxylase, PSD1, respectively, demonstrated that both lipids are required for mitochondrial morphology and fusion (5).…”
mentioning
confidence: 99%
“…chondrial morphology and reduced growth under respiratory conditions caused by dramatically reduced PE levels in mitochondrial and other cellular membranes (44,45). For this reason, functional Psd1 is highly important to maintain cell integrity and function.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this translocation process involves membrane contact sites like the endoplasmic reticulum-mitochondria tethering complex ERMES is under debate (41)(42)(43). Deletion of PSD1 leads to ethanolamine auxotrophy during growth on non-fermentable carbon sources, reduced growth on fermentable media, and morphological alterations of mitochondria (44,45). Moreover, Psd1 is required for the regulation of pleiotropic drug resistance by inducing PDR5 gene expression (46).…”
mentioning
confidence: 99%
“…Mol Cell Biochem and phosphatidylglycerol (PG) have overlapping functions [4,7,28] and the Dga1 activity was also unaffected in the presence of PE and PG (data not shown). As CL did not affect the Dga1 enzymatic activity in vitro, therefore, to assess the role of CL on Dga1 activity in vivo, we performed the BODIPY TM 493/503 staining of the LDs from different genetic backgrounds overexpressing the His-tagged Dga1 protein.…”
Section: Cardiolipin Does Not Affect Dga1 Acyltransferase Activitymentioning
confidence: 79%